Civilizational Clash or Balderdash? The Causes of Religious Discrimination in Western and European Christian-Majority Democracies. Issue 1 (2nd January 2019) - Fox, Jonathan
Abstract: Samuel Huntington predicted that conflict, including domestic conflict, will be more common between civilizations than within them, that the Islamic civilization will be especially violent, and that Islamic-Western conflict will be particularly intense. This study seeks to test this proposition focusing on societal and governmental religious discrimination against 156 religious minorities in 36 European and Western Christian-majority democracies using data from the Religion and State-Minorities round 3 (RASM3) dataset. It also contrasts Huntington's predictions with predictions of three other literatures: the securitization of Islam, anti-cult policies, and anti-Semitism. The findings show that these three literatures are a better fit for explaining religious discrimination in these countries than is Huntington's "clash of civilizations" theory.